Partisipasi Penyusunan Anggaran, Kompetensi, Self-Efficacy Sistem Pengukuran Kinerja dan Kinerja Manajerial - Gitariani, Ni Kadek Dwi; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi, 2021)
The purpose of this study was to examine the effect of budgeting participation, competence, self-efficacy and performance measurement systems on managerial performance. This research was conducted at the Regional Apparatus Organization (OPD) of Tabanan Regency. This research was conducted at the Regional Apparatus Organization (OPD) of Tabanan Regency. A total of 102 people were selected as respondents. The sampling method used in this study was purposive sampling and the data analysis technique used in this study was multiple linear regression analysis. The results of this study indicate that budgetary participation, competence, self-efficacy and performance measurement systems have a positive effect on managerial performance. Keywords: Participation in Budget Formulation; Competence, Self-Efficacy; Performance Measurement System; Managerial Performance.